106 Reimbursement Trends in Neuroendovascular Interventions 2013-2022. (April 2023) - Steiger, Kyle; Singh, Rohin; Koester, Stefan Wolfgang; Nguyen, Brandon; Brown, Nolan James; Shahrestani, Shane; Catapano, Joshua; Srinivasan, Visish M.; Gendreau, Julian Lassiter; Patel, Naresh P.; Erben, Young
Abstract : INTRODUCTION: Neuroendovascular surgeries are increasingly important, particularly with the advent of thrombectomy as the gold standard in the management of large vessel stroke. METHODS: The Physician Fee Schedule Look-Up Tool was queried from 2013 to 2019 for all primary Current Procedural Terminology (CPT) codes identified by the American Medical Association as pertaining to endovascular procedures of the nervous system (61623, 61624, 61630, 61635, 61626, 61645, and 61650). The facility prices were averaged for each procedure and subsequently adjusted for inflation using the United States Bureau of Labor Statistics' Consumer Price Index Inflation Calculator as adjusted to January of 2022. Statistical analyses, including data aggregation, exploratory analysis, and propensity adjustment, were performed using R, version 4.0.1 (The R Foundation, Vienna, Austria). The two-sided Mann-Kendall trend test, a non-parametric statistical test that assesses for monotonic trends in either an upward or downward trend, was utilized to assess for trends over time. Within each year analyzed, a Chi-squared test for trend in proportions was used. A significance level of 0.05 was used. RESULTS: Decreases in reimbursement were noted for all neuroendovascular procedures. This trend was statistically significant for temporary balloon occlusion, CPT61623 (2013:$677.04; 2022:586.96; p: 0.01), central nervous system transcatheter permanent occlusion or embolization, CPT61624 (2013:$1349.61; 2022:$1175.02; p: 0.02), non-central nervous system transcatheter permanent occlusion or embolization, CPT61626 (2013:$1040.86; 2019:$912.29; p: 0.002), stent placement, CPT61635 (2013:$1697.18; 2022:$1490.68; p: 0.05), and when viewed as aggregate procedures (2013:$1265.01; 2022:$1000.45; p < 0.01). CONCLUSIONS: Inflation-adjusted reimbursement is decreasing for certain neuroendovascular procedures over time and for all neuroendovascular procedures when viewed as an aggregate group. This suggests a need for reevaluation of the market value and advocacy for neuroendovascular providers and procedures in the era of value/quality-based care.